2018
DOI: 10.7150/thno.27454
|View full text |Cite
|
Sign up to set email alerts
|

Take a Deep Breath - Monitoring of Inhaled Nanoparticles with Magnetic Particle Imaging

Abstract: Magnetic Particle Imaging (MPI) is a new imaging modality based on the visualization of Superparamagnetic Iron Oxide Nanoparticles (SPIONs) using magnetic fields. The potential of MPI was recently evaluated in numerous ex vivo and in vivo studies and the technique can now be considered as an established preclinical imaging modality with a promising perspective of clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…159 When taken with the results from Zhou et al, 27 the authors demonstrated a proof-of-concept for MPI-based perfusion-ventilation mapping. 341 This mapping has been applied clinically using other modalities, for the diagnosis of PE and in preoperative evaluation of the lungs. The rate of cancer curing almost directly correlates with the stage at which it is diagnosed, meaning that if it was diagnosed and provided with appropriate treatment at an earlier stage, the cure rate would increase significantly.…”
Section: Perfusion Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…159 When taken with the results from Zhou et al, 27 the authors demonstrated a proof-of-concept for MPI-based perfusion-ventilation mapping. 341 This mapping has been applied clinically using other modalities, for the diagnosis of PE and in preoperative evaluation of the lungs. The rate of cancer curing almost directly correlates with the stage at which it is diagnosed, meaning that if it was diagnosed and provided with appropriate treatment at an earlier stage, the cure rate would increase significantly.…”
Section: Perfusion Imagingmentioning
confidence: 99%
“…158 When taken with the results from Zhou et al , 27 the authors demonstrated a proof-of-concept for MPI-based perfusion–ventilation mapping. 340 This mapping has been applied clinically using other modalities, for the diagnosis of PE and in preoperative evaluation of the lungs.…”
Section: Primary Biomedical Applications Of Mpimentioning
confidence: 99%
“…Magnetic particle imaging (MPI) is an emerging tomographic method that uses superparamagnetic iron oxide nanoparticles (SPIONs) as imaging agents 12 - 14 . Since its first introduction in 2005 15 , high mass sensitivity (Fe nanograms), high spatial resolution (sub-mm), zero tissue depth signal attenuation, and lack of ionizing radiation have been reported as advantages of MPI 16 .…”
Section: Introductionmentioning
confidence: 99%
“…MPI does not use ionizing radiation and SPIO tracers have a long shelf life ex vivo, while they break down in vivo, with iron being incorporated into hemoglobin and ferritin. [14][15] In addition, images obtained from MPI can be coregistered with other modalities, like computed-tomography (CT) and MR. Proof-of-principle studies have explored the application of MPI for blood pool imaging, [16][17][18][19][20] lung perfusion, [21][22][23] bleed detection, [24][25] and tracking of nanoparticle accumulation in cancer tumors. [26][27] .…”
Section: Introductionmentioning
confidence: 99%